ANALISIS KESELAMATAN KERJA DALAM PELAKSANAAN SURVEI PENGENDALIAN HAMA DAN PENYAKIT IKAN AIR TAWAR - Muhammad Fachri (Jurnal Akuakultur Rawa Indonesia, 2021)
Survey implementation is a way to get data of controlling fish pests and diseases. The impact of fish pests and diseases attacked cause of losses for aquaculture activity. However, there is no job safety analysis in implementation survey of fish pest and disease management. The aim of this study was to determine the job safety analysis in implementation survey to control fish pests and diseases. This research was conducted in 7 regencies/cities in Bangka Belitung Province from February to September 2021. This research used descriptive qualitative survey. Data collected by Walk Through Survey (WTS), interviews and documentation. Then, analyzed with Job Safety Analysis so the level of risk and impact on job safety can be assessed. The results of this study are the implementation survey of fish pests and disease management has low to high risk of work accidents. Some control efforts such as through administration, substitution and personal protective equipment (PPE) can prevent to work accidents.Key words : Analysis, Fishery, Job, Safety.